Islam in the African American Community: Negotiating between Black Nationalism and Historical Islam - Chande, Abdin (Islamic Studies, 2008)
This paper traces the trajectory of the African American Muslim community in the US by analyzing the various strands of the community's make-up and exploring the dialectic of immigrant-indigenous Islam. It raises questions regarding, for instance, the failure of the community to create a group of qualified scholars in three decades. Such scholars, it is argued, are the instrument through which new forms of religious expressions can emerge and new and different voices can be heard as more conceptual and even gender spaces open up. Finally, the paper discusses the challenges facing the Ummah/Muslim community from within — the cultural, racial and class-based divides — and from without — the impact of 9/11 against which a beleaguered community must now, to some extent, define its faith.